Social entrepreneurship as a panacea for insecurity challenges in northern Nigeria - Sagagi, Murtala S.; Inusa, Auwalu (2014)
The myriad of problems facing Northern Nigeria, especially high poverty incidence, illiteracy, economic inequality, and conflicts cannot be adequately overcome by the government alone. There is the urgent need for an alternative community intervention mechanism to compliment government’s efforts in confronting social problems on sustainable basis. Today, Social Entrepreneurship is considered critical in achieving vital socio-economic objectives in nations worldwide. Unfortunately, the subject has not received adequate attention in academic and policy discussions in Nigeria.This paper, therefore, is aimed at examining the concept of Social Entrepreneurship in the Nigerian context and also shows how innovative social interventions have assisted in reducing the menace of insecurity problems in Northern Nigeria.The analysis conducted in the paper has benefited extensively from contemporary literature on the subject, observations and interviews with members of three community organisations in northern Nigeria. Accordingly, the paper found that social entrepreneurship has not been fully understood in Nigeria, even though the activities of social groups have tremendously help in reducing the problem of insecurity bedevilling the region. The community organisations observed lacked proper organisation, funding and capacity.With better enlightenment and sensitisation, coupled with improved capacity to generate and manage funding, community organisations will be in better position to augment government’s initiative in restoring peace and security in the northern Nigeria.